Abnormal Adrenal Mass Presents as Proximal Epithelioid Sarcoma. (23rd September 2020) - Martinez, Valeria Pereira; Nicholson, Marilin; Patel, Trushar
Abstract : Epithelioid sarcoma (ES) is a rare malignant mesenchymal neoplasm that accounts for less than one percent of all soft-tissue sarcomas. Only two cases of ES involving the adrenal gland were found after a literature review. We report a case of an 82-year-old female initially presenting with right flank pain who was subsequently found to have an incidental left adrenal mass on CT imaging. After appropriate diagnostic workup, the patient underwent surgical resection. A diagnosis of ES was made from the histopathological analysis. The characteristic findings of ES are epithelioid cells with rhabdoid morphology and moderate eosinophilic cytoplasm. Immunohistochemical findings are significant for positive staining for epithelial markers, cytokeratins, vimentin, and CD34, and loss of INI-1 stain. Due to the aggressive nature and limited data of ESs, the standard treatment continues to remain wide surgical excision.